Building an evaluation model for the motor health of preschool-aged children from the perspective of interdisciplinary integration - Dongxu Du; Linyan Chai; Gao Yang; Xiang Ao (Frontiers in Psychology)
IntroductionThis study explored a structural equation model of preschool children’s sports health levels and revealed the coupling effect of many factors on children’s sports health levels. Despite the importance of motor health in early childhood, a comprehensive evaluation model integrating multiple health dimensions remains underexplored.MethodsWPS Office 6.4 and IBM® SPSS® Statistics 26.0 were used to analyze the data, and the statistical significance level was set at p-value < 0.05. IBM® SPSS® Amos™ 24.0 was used to analyze the data and develop a structural equation model for children’s motor health.ResultsThe total motor health scores of the preschoolers showed highly significant positive correlations (p-value < 0.01) at the 0.01 level (two-tailed) with motor ability, physical health, mental health, social and emotional competence, motor health environment, and motor health behavior. Through the evaluation and verification of the fitness of the whole and multi-group structural equation models, it can be seen that the significance probability values of the preset theoretical model are p-value > 0.05, RMSEA < 0.05, GFI > 0.90, and AGFI > 0.90, which supports the hypothesis of nothingness. NFI > 0.90, IFI > 0.90, TLI > 0.90, and CFI > 0.90. All indices of value-added fitness met the acceptable standards of the model, and the model met the standard of simple adaptation.ConclusionA structural equation model of preschool children’s motor health was constructed, which passed the fitness test and is stable, adaptable, and widely applicable. These findings can help educators design evidence-based physical activity programs to enhance preschoolers’ motor and overall health.